Optimizing Food Diversification through Learning from Successful Implementation in Indonesia - Yanti, Dwi Krusita; Choiriyah, Ilmi Usrotin (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the implementation of food consumption diversification policies in Sidoarjo district, using George C. Edwards III's theory on communication and bureaucratic structure. Employing a descriptive qualitative approach, the research utilizes primary data from field surveys and interviews, and secondary data from official sources. The findings show that 14 out of 18 sub-districts successfully implemented these policies, leading to improved and diverse food consumption patterns as measured by the Food Hope Pattern (PPH) score. Effective communication, adequate resources, strong commitment, and structured bureaucracy were key to this success. The study highlights the importance of these factors in enhancing food security and nutritional outcomes at the local level. Highlights: Effective Communication: Essential for policy success in 14 sub-districts. Resource Adequacy: Crucial human, financial, and facility resources. Structured Bureaucracy: Clear roles and processes enhance outcomes. Keywords: food diversification, food security, Sidoarjo, implementation, qualitative research